2015
DOI: 10.1063/1.4906299
|View full text |Cite
|
Sign up to set email alerts
|

Internal wave boundary layer interaction: A novel instability over broad topography

Abstract: It has been known for some time that internal wave-induced currents can drive near bed instabilities in the bottom boundary layer over a flat bottom. When the bottom is not flat, the situation can become quite complicated, with a diverse set of mechanisms responsible for instability and the subsequent transition to turbulence. Using numerical simulations, we demonstrate the existence of a mode of instability due to internal solitary wave propagation over broad topography that is fundamentally different from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The localized material transport due to the flow separation is more comparable to our observations, however, the horizontal transport of near-wall material is substantial (see figure 6 b ) compared to the vertical transport of a few boundary layer widths in Harnanan et al. (2015). Harnanan et al.…”
Section: Discussionsupporting
confidence: 87%
“…The localized material transport due to the flow separation is more comparable to our observations, however, the horizontal transport of near-wall material is substantial (see figure 6 b ) compared to the vertical transport of a few boundary layer widths in Harnanan et al. (2015). Harnanan et al.…”
Section: Discussionsupporting
confidence: 87%
“…Theoretical work also suggests that there is likely to be significant exchange between the bottom boundary layer and the main water column (cf. Harnanan et al, 2015).…”
Section: Figure 8 Locationmentioning
confidence: 99%
“…In the second paper where the results are extended to both waves of depression and elevation, quantitative measurement of energy loss of due to wave-bottom topography interaction is calculated for different regimes. For smooth topography with much more gentle slopes, Harnanan et al (2015) performed three-dimensional simulations and showed that there exist two qualitatively different modes of instability. The first is a separation instability, which leads to strong, localized vortex roll-up.…”
Section: Introductionmentioning
confidence: 99%